Worldwide prevalence of physical inactivity calls for worldwide actions. - Bélanger, M; Foster, C (2011)
OBJECTIVE: This commentary offers a discussion of the paper by Dumith et al. published in this issue of Preventive Medicine. METHODS: We discuss the added value of the manuscript by Dumith et al. while acknowledging some limitations of the analyses. RESULTS: We argue that there is a global and urgent need to take action against physical inactivity. CONCLUSION: The paper by Dumith et al. provides context to help build the case for better public health organization and effort to tackle physical inactivity at a worldwide level.